2021
DOI: 10.1038/s41591-021-01540-1
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of protection against symptomatic and asymptomatic SARS-CoV-2 infection

Abstract: The global supply of COVID-19 vaccines remains limited. An understanding of the immune response that is predictive of protection could facilitate rapid licensure of new vaccines. Data from a randomized efficacy trial of the ChAdOx1 nCoV-19 (AZD1222) vaccine in the United Kingdom was analyzed to determine the antibody levels associated with protection against SARS-CoV-2. Binding and neutralizing antibodies at 28 days after the second dose were measured in infected and noninfected vaccine recipients. Higher leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

44
732
6
9

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 1,012 publications
(791 citation statements)
references
References 40 publications
44
732
6
9
Order By: Relevance
“…18 Furthermore, a previous study in humans found that anti-RBD IgG levels of 506 BAU/ml correlated with protection against symptomatic SARS-CoV-2 infection against B.1.1.7 (alpha variant). 19 The CV-AZ regimen could achieve more than 506 BAU/mL similar to that induced by the AZ-AZ regimen but within a shorter time period, suggesting that the heterologous CV-AZ regimen could be used as an alternative to the proven efficacy of the CV-CV and AZ-AZ regimen in the general population.…”
Section: Discussionmentioning
confidence: 92%
“…18 Furthermore, a previous study in humans found that anti-RBD IgG levels of 506 BAU/ml correlated with protection against symptomatic SARS-CoV-2 infection against B.1.1.7 (alpha variant). 19 The CV-AZ regimen could achieve more than 506 BAU/mL similar to that induced by the AZ-AZ regimen but within a shorter time period, suggesting that the heterologous CV-AZ regimen could be used as an alternative to the proven efficacy of the CV-CV and AZ-AZ regimen in the general population.…”
Section: Discussionmentioning
confidence: 92%
“…There is currently no agreed correlate of protection, but it has been suggested that, in a study of AZD122, an average level of 40,923 arbitrary units (a.u. )/mL 4 weeks after the second dose for anti-S IgG using the MSD assay used in this study, equivalent to 264 binding Ab units (BAUs)/mL using the World Health Organization (WHO) international standard, is associated with 80% protection from symptomatic infection for the population of recipients receiving that vaccine regimen (Feng et al, 2021). However, this was predominantly against the alpha variant.…”
Section: Discussionmentioning
confidence: 96%
“…Viral variants such as delta (B.1.167.2) may also affect the protective efficacy of the generated immune responses (Reuters, 2021). We currently lack clear correlates of protection against SARS-CoV-2, although recent attempts to compare vaccines have given some indication of binding and neutralizing antibody measures that accompany efficacy (Earle et al, 2021;Feng et al, 2021;Khoury et al, 2021). Importantly, large-scale clinical trial data, on which these estimates are based, do not include measures of T cells.…”
Section: Introductionmentioning
confidence: 99%
“…Levels of binding and neutralizing antibodies correlate with vaccine efficacy for both mRNA and adenovirusvectored vaccines, and likely have utility in predicting efficacy after boosting. [9][10][11][12] A homologous booster with 30μg BNT162b2 increased neutralizing antibody titers against wild-type virus and the Delta variant to more than 5 times as high as after dose 2. 13 A booster injection of 50 µg of mRNA-1273 increased neutralizing antibody titers against wild-type virus and the Delta variant 3.8-fold and 2.1-fold higher, respectively, than after the primary series.…”
Section: Introduction: (2690 Words -2700 Allowable)mentioning
confidence: 98%